Automated virtual reality (VR) therapy (gameChange) treating agoraphobic avoidance and distress in patients with psychosis: a multicentre, parallel group, single-blind, randomised controlled trial in England with mediation and moderation analyses - Freeman, D; Lambe, S; Kabir, T; Kabir, T; Petit, A; Rosebrock, L; Yu, L; Galal, U; Grabey, J; Rovira, A; Clark, D; Waite, F (Elsevier, 2022)
Background: Automated delivery of psychological therapy using immersive technologies such as virtual reality (VR) might greatly increase the availability of effective help for patients. We aimed to evaluate the efficacy of an automated VR cognitive therapy (gameChange) to treat avoidance and distress in patients with psychosis, and to analyse how and in whom it might work.